AKUNTANSI LINGKUNGAN SEBAGAI STRATEGI PENGELOLAAN LINGKUNGAN DAERAH WISATA BANGKA BOTANICAL GARDEN (BBG) PANGKALPINANG - Zakia Ayu Lestari (Budgeting: Jurnal Akuntansi Syariah, 2022)
The purpose of this study was to explore Environmental Accounting as a management strategy for the Bangka Botanical Garden (BBG) tourist park. BBG is one of the artificial-based natural tourism (processed from former mining areas), which has attracted many tourists to visit. However, with the increasing image of BBG in Bangka Belitung, of course, it will also increase the number of tourists visiting BBG, both tourists from the Bangka Belitung Islands Province itself, as well as from outside. An increase in the number of tourists will also have an impact, both positive and negative impacts. So it needs proper management so that BBG can become a sustainable natural tourism area. This study uses a qualitative method with data collection through the distribution of questionnaires in the form of questionnaires, observations, and collection of related documents which are then analyzed. The results of this study are to find out that environmental accounting is the right strategy in managing the BBG tourism environment.